Pelatihan Strategi Pemasaran Berbasis Digital Pada Produk Pertanian di Desa Sisarahili Sisambualahe - Otanius Laia; Febriani Lase; Hendra Saro Telaumbanua; Dermawan Telaumbanua; Siskania Hulu; Andy Rahmad Rainang; Arif Rianto Zai; Sinema Utama Zebua; Gracesa Kristin Ziliwu; Safriyus Bate'e; Frans Aria Putra Zebua (Jurnal Visi Pengabdian Kepada Masyarakat, 2025)
Training on digital-based marketing strategies for agricultural products was conducted in response to the challenges of marketing agricultural products in the increasingly competitive digital era. Many agricultural businesses still face limited knowledge and skills in utilizing digital technology to market their products more widely and efficiently. The objective of this training was to increase participants' capacity in understanding digital marketing concepts, promotional techniques through social media, the use of marketplaces, and agricultural product branding strategies to increase consumer awareness. The training method included theoretical material, case studies, simulations of digital platform use, and interactive question-and-answer sessions. The training participants included farmers, farmer groups, and agribusinesses. The results showed a significant increase in participants' understanding of digital marketing strategies, with most participants feeling more confident in starting to market their products through online platforms. Furthermore, this training also encouraged participants to be more creative in creating attractive promotional content that aligns with the characteristics of the agricultural products being sold. Therefore, this training is expected to be the first step in strengthening the competitiveness of agricultural products in the modern market and contributing to increasing the income and welfare of agricultural businesses.